Answer:
1190
Step-by-step explanation:
<u>Define x:</u>
Let one of the numbers be x.
The other number is x + 2
<u>Construct equation:</u>
<span>twice the smaller is 16 more than the larger
</span>⇒2x = x + 2 - 16
<u>Solve x:</u>
2x = x + 2 - 16
x = -14
<u>Find the two numbers:</u>
Smaller number = x = -14
Larger number = x + 2 = -12
Answer: The two numbers are -14 and -12
Answer:
a, -b
Step-by-step explanation:
When x is a, the function becomes
![f(a)=3(a-a)(a+b)](https://tex.z-dn.net/?f=f%28a%29%3D3%28a-a%29%28a%2Bb%29)
as you see, a-a is 0, and as your whole function is multiplied by this, it makes it 0.
![f(-b)=3(-b-a)(-b+b)](https://tex.z-dn.net/?f=f%28-b%29%3D3%28-b-a%29%28-b%2Bb%29)
As you see -b+b is 0, and once again, this would make the whole function 0.
Answer:
m < -6
Step-by-step explanation:
plz can u mark brainliest if correct. thank you so much.